Reflexiones al final de un inicio: estudio de asociación entre variables sociodemográficas y tipo de parto en la prevención de la violencia obstétrica en España - Cristina Benlloch-Doménech; María José Barbé-Villarubia; Jorge Cascales-Ribera (Universitat de Barcelona, 2019)
The aim of our work is to approach types of childbirth at the end of pregnancy from a sociodemographic point of view, with special emphasis in the number of C sections. Material and Method: The birth data in Spain provided by the National Institute of Statistics has been analyzed. Results: The results obtained from crossing the variables show that there are social determinants that should be considered in order to better understand the process of childbirth. Discussion: Our approach goes beyond the mere description and aims to show a causality that should be included in obstetric protocols. Conclusion: Health workers must be aware of the personal circumstances of the patients so that the delivery develops as easily as possible, taking into account the characteristics of the woman, and being not so much concerned with the number of cesarean sections they have to perform.